PENEGAKAN HUKUM OLEH KEPOLISIAN TERHADAP PELAKU PENANGKAPAN IKAN DENGAN MENGGUNAKAN PUKAT HARIMAU (TRAWL) DI WILAYAH PESISIR KABUPATEN BENGKALIS. - Elsera Yozani, H Riyanda; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Bengkalis Regency waters is known for the marine resourches, especially fisheries. It causes a lot of Indonesian and foreign fisherman who fish in these waters illegally. Law enforcement againts criminal offense for the using of the trawl in Bengkalis regency has not been able to be conducted well, because of the obstacles faced by the law enforcement both in the field and those that are technical and non-technical. The purpose of this research is to investigate the implementation of law enforcement againts againts criminal offense for the using of trawl according to Undang-undang No. 45 Tahun 2009 on fisheries in Bengkalis Police Resort, to determine obstacles in the implementation of law enforcement againts the criminal act, as well as to know the efforts made to overcome the obstacles.This research was conducted by using sociological research. The data used in this reasearch is primary data (data obtained directly from respondents through interviews. The primary data is in the form of factors that cause criminal acts in the fisheries area of Bengkalis Police Resort Jurisdiction). The data collection technique in this research is: interview, that means conducting direct interviews technique with responndents regarding the problems studied.The implementation of law enforcement againts criminal offense for the using of pukat harimau is done by both preventive and repressive acts. But in reality, the law enforcement in the field of fisheries has not yet received a bright spot in revealing any criminal offense for the using of pukat harimau. The writer suggests that, first, in conducting law enforcement againts criminal offense for the using of trawl the Police must increase the number of Police personnel because of the breadth of the territorial waters of which covers ine district, second, in facing any crime that occures the Police needs to add more facilities and infrastuctures required to carry out law enforcement, third, the law enforcement againts criminal offenses in Bengkalis is a common responsibillity, then law enforcement must go hand in hand with coastal communities and coordinate well so that a criminal offense for the using of trawl can be minimized.Keywords: Implementation-Enforcement-Criminal Act-Trawl-Police